In vitro evaluation of casein phosphopeptide-amorphous calcium phosphate effect on the shear bond strength of dental adhesives to enamel - Niloofar Shadman; Shahram Farzin Ebrahimi; Maryam Azizi Shoul; Hasti Sattari (Wolters Kluwer Medknow Publications, 2015)
Background: Casein phosphopeptide-amorphous calcium phosphate (CPP-ACP) is applied for remineralization of early caries lesions or tooth sensitivity conditions and may affect subsequent resin bonding. This in vitro study investigated the effect of CPP-ACP on the shear bond strength of dental adhesives to enamel. Materials and Methods: Sixty extracted human molar teeth were selected and randomly divided into three groups and six subgroups. Buccal or lingual surfaces of teeth were prepared to create a flat enamel surface. Adhesives used were Tetric N-Bond, AdheSE and AdheSE One F. In three subgroups, before applying adhesives, enamel surfaces were treated with Tooth Mousse CPP-ACP for one hour, rinsed and stored in 37°C temperature with 100% humidity. This procedure was repeated for 5 days and then adhesives were applied and Tetric N-Ceram composite was adhered to the enamel. This procedure was also fulfilled for the other three subgroups without CPP-ACP treatment. After 24 hour water storage, samples were tested for shear bond strength test in a universal testing machine. Failure modes were determined by stereomicroscope. Data were analyzed by t-test and one-way analysis of variance with P < 0.05 as the level of significance. Results: In comparison between applied and non-applied CPP-ACP subgroups, there was no significant decrease in the shear bond strength to enamel only in Tetric N-Bond (P > 0.05). In non-applied CPP-ACP subgroups, there were statistically significant differences among all subgroups. Tetric N-Bond had the highest and AdheSE One F had the lowest shear bond strength. Conclusion: CPP-ACP application reduces the shear bond strength of AdheSE and AdheSE One F to enamel but not Tetric N-Bond.